2004
DOI: 10.1901/jaba.2004.37-27
|View full text |Cite
|
Sign up to set email alerts
|

On the Relative Contributions of Noncontingent Reinforcement and Escape Extinction in the Treatment of Food Refusal

Abstract: In the current investigation, we evaluated the relative effects of noncontingent reinforcement (NCR), escape extinction, and a combination of NCR and escape extinction as treatment for the feeding problems exhibited by 4 children. For each participant, consumption increased only when escape extinction was implemented, independent of whether NCR was present or absent. These results were consistent with prior research suggesting that positive reinforcement alone is insufficient for increasing consumption, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
134
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(145 citation statements)
references
References 26 publications
9
134
2
Order By: Relevance
“…It should be noted, however, that several of the strategies reviewed in this paper have also been shown to be ineffective in the absence of EE (e.g., Najdowski, Wallace, Doney, & Ghezzi, 2003;Patel, Reed, Piazza, Bachmeyer, & Layer, 2005;Reed et al, 2004). It is hoped, however, that these guidelines will assist practitioners in selecting caregiver-friendly treatments that can be implemented in community settings as first line treatments, thus reducing the need for tertiary care for some children.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…It should be noted, however, that several of the strategies reviewed in this paper have also been shown to be ineffective in the absence of EE (e.g., Najdowski, Wallace, Doney, & Ghezzi, 2003;Patel, Reed, Piazza, Bachmeyer, & Layer, 2005;Reed et al, 2004). It is hoped, however, that these guidelines will assist practitioners in selecting caregiver-friendly treatments that can be implemented in community settings as first line treatments, thus reducing the need for tertiary care for some children.…”
Section: Discussionmentioning
confidence: 91%
“…Preferred toys or activities are the most common stimuli used when NCR is utilized in the treatment of feeding problems (Reed et al, 2004;Wilder, Normand, & Atwell, 2005). Wilder et al, for example, examined the use of NCR to decrease self-injury and increase food acceptance in a child who exhibited inadequate and selective food intake and who had been diagnosed with developmental disabilities.…”
Section: Noncontingent (Positive) Reinforcement (Ncr)mentioning
confidence: 99%
“…Correspondence was relatively high; however, one potential limitation of this study is that it is not clear if descriptive assessments are sufficient to thoroughly assess the functions of IMB and prescribe an effective treatment, although previous research has demonstrated the effectiveness of treatments for IMB without the benefit of a functional analysis (e.g., Patel et al, 2002;Reed et al, 2004). We did not evaluate functionbased interventions in this study, but all treatments were designed based on both the descriptive assessment and functional analysis (available from first author upon request).…”
Section: Discussionmentioning
confidence: 95%
“…It has been shown frequently that escape is the most common reinforcer for food refusal and that the most effective treatments typically include some component to prevent the child from avoiding the food presented (Bachmeyer, 2009;Cooper et al, 1995;Piazza, Patel, Gulotta, Sevin & Layer, 2003;Williams, Field, & Seiverling, 2010). In addition, even when other reinforcers such as attention and tangibles have been identified, the necessary component to an effective intervention has been shown to be escape extinction, suggesting that any positive reinforcers identified may augment the effects of treatment but may not be solely sufficient to increase food acceptance (Patel, Piazza, Martinez, Volkert, & Santana, 2002;Reed et al, 2004).…”
mentioning
confidence: 99%
“…In turn, those in the Positive Incentive condition were expected to report higher arousal levels than those in the No Incentive condition, as the former group is provided with a stronger motivation to recall accurately or fabricate convincingly the admission than those in the No Incentive group. These predictions are also based on the general finding that negative reinforcements are more effective in inducing short term changes in behaviours than positive incentives (e.g., Bloom et al, 2007;Fagerström et al, 2007;Iwahara & Tanabe, 1963;Jones, 1961;Meyer & Offenbach, 1962;Piazza, Patel, Gulotta, Sevin, & Layer, 2003;Reed et al, 2004). Negative reinforcement may be superior because avoiding negative events typically exerts greater changes in emotion, arousal, and memory than experiencing positive events (Magoon & Critchfield, 2008).…”
Section: Hypotheses: Manipulation Checksmentioning
confidence: 99%